Hots-Based Learning in 2013 Curriculum: Is it Suitable? - Pratiwi, Nita; Mustadi, Ali (Jurnal Pendidikan Indonesia, 2021)
This study aims to evaluate the suitability of the HOTS-based learning process with the Minister of Education and Culture Regulation Number 22 of 2016. This study is an evaluation study with Stake Countenance Models. Evaluation is carried out through evaluation stages, namely: Antecedent stage; Process Stage (transaction); and Outcomes stage. Respondents in this study were 98 people who were selected using the Stratified Random Sampling technique. The results showed that HOTS-based learning has not been fully achieved, namely for the implementation of HOTS in the 2013 curriculum in the incomplete category at 3%; a quite complete category at 9.44%; a complete category at 62.44%; and a very complete category at 25.11%. So, can be concluded that not all HOTS-based learning processes have been implemented suitable with the Minister of Education and Culture Regulation Number 22 of 2016.